2022
DOI: 10.1001/jamapediatrics.2021.4829
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Interventions to Prevent Physical and Sexual Dating Violence Among Adolescents

Abstract: IMPORTANCE Sexual and physical dating violence is prevalent among adolescents and is associated with adverse health effects.OBJECTIVE To conduct a systematic review and meta-analysis of randomized clinical trials to assess the efficacy of prevention programs for sexual and physical dating violence in adolescents.DATA SOURCES Search terms were combined for dating violence, adolescents, and randomized clinical trials in PsycINFO/Eric/PsycArticles, PubMed, and Web of Science databases from inception through April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Results showed that prevention programs delivered both in a school setting and targeting adolescents aged 15 to 19 years yielded significantly larger effect sizes, compared with programs delivered in other contexts (eg, community agencies) or involving younger adolescents. This finding is consistent with a previous meta-analysis on teen dating violence, 12 which reported larger effect sizes for older adolescents. The trajectory of sexual violence, which tends to increase as adolescents become older, may help explain this finding.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Results showed that prevention programs delivered both in a school setting and targeting adolescents aged 15 to 19 years yielded significantly larger effect sizes, compared with programs delivered in other contexts (eg, community agencies) or involving younger adolescents. This finding is consistent with a previous meta-analysis on teen dating violence, 12 which reported larger effect sizes for older adolescents. The trajectory of sexual violence, which tends to increase as adolescents become older, may help explain this finding.…”
Section: Discussionsupporting
confidence: 93%
“… 45 Furthermore, these findings are promising, given the conclusions from previous literature reviews. 12 , 13 Review articles about the prevention of sexual violence that focused primarily on college-aged youth and older individuals consistently described a lack of compelling evidence for program associations on self-reported experience and perpetration of sexual violence. 46 , 47 , 48 Thus, sexual violence prevention programs targeted at adolescents may have a greater impact than programs targeted at older individuals, such as college students or adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Community level interventions, including discrete adolescent dating violence prevention programs, delivered in diverse community settings including schools, sports practices, and others, decreased AYAMs’ experiences of sexual violence [44]. In a meta-analysis, recent adolescent dating violence prevention programs overall demonstrated a nonstatistically significant decrease in sexual violence experiences, suggesting further investigation into community level prevention and intervention work is necessary to stop sexual violence cycles [45 ▪▪ ]. The literature also describes community-based gender transformative programing that ‘challenge[s] patriarchal masculinity and power inequalities at multiple levels and advocate[s] for gender justice’ [28] including Manhood 2.0, and work done through MenEngage Alliance and Promundo.…”
Section: Intervention and Preventionmentioning
confidence: 99%